Freeze-dried chitosan-platelet-rich plasma implants improve supraspinatus tendon attachment in a transosseous rotator cuff repair model in the rabbit. (January 2019) - Deprés-Tremblay, Gabrielle; Chevrier, Anik; Snow, Martyn; Rodeo, Scott; Buschmann, Michael D
Rotator cuff tears result in shoulder pain, stiffness, weakness and loss of motion. After surgical repair, high failure rates have been reported based on objective imaging and it is recognized that current surgical treatments need improvement. The aim of the study was to assess whether implants composed of freeze-dried chitosan (CS) solubilized in autologous platelet-rich plasma (PRP) can improve rotator cuff repair in a rabbit model. Complete tears were created bilaterally in the supraspinatus tendon of New Zealand White rabbits ( n  = 4 in a pilot feasibility study followed by n  = 13 in a larger efficacy study), which were repaired using transosseous suturing. On the treated side, CS-PRP implants were injected into the transosseous tunnels and the tendon itself, and healing was assessed histologically at time points ranging from one day to two months post-surgery. CS-PRP implants were resident within transosseous tunnels and adhered to tendon surfaces at one day post-surgery and induced recruitment of polymorphonuclear cells from 1 to 14 days. CS-PRP implants improved attachment of the supraspinatus tendon to the humeral head through increased bone remodelling at the greater tuberosity and also inhibited heterotopic ossification of the supraspinatus tendon at two months. In addition, the implants did not induce any detectable deleterious effects. This preliminary study provides the first evidence that CS-PRP implants could be effective in improving rotator cuff tendon attachment in a small animal model.